Teori Interpretasi Nasr Hamid Abu Zayd - Fikri Hamdani (LPPM IAIN Sultan Amai Gorontalo, 2016)
This paper describes the thought of Nasr Hamid Abu Zayd on the theory of interpretation/method of interpretation of the al-Qur’an, the discussion of which is the study of descriptive-analitif. In the method, Nasr Hamid seeks to reveal the meaning and significance (maghza) with the meaning of